Analisis Pengembangan Karir, Motivasi dan Kepuasan Kerja Terhadap Kinerja Karyawan di PT Dreams Tour & Travel - Aloysius Amavisca; Gendut Sukarno (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to examine the concept of Career Development, Motivation and Job Satisfaction on Employee Performance at PT Dream Tours & Travel Surabaya. This research is expected to provide input to the company in managing employee performance, especially related to Career Development, Motivation and Job Satisfaction. The object of this research is PT. Dream Tours & Travel Surabaya, with primary and secondary data sources. The population in this study were 55 employees of PT Dream Tours & Travel Surabaya with a saturated sample technique of 55 employees as respondents. The analysis technique used in this research is Partial Least Square (PLS) 4.0 with the testing tools used are Outer Model Test, Inner Model Test and Hypothesis Test. The test results show that there is a significant influence between career development on employee performance, as well as a significant influence between motivation on employee performance, and a significant influence between job satisfaction on employee performance.